Synergy Between Microbial Inoculants and Mineral Fertilization to Enhance the Yield and Nutritional Quality of Maize on the Peruvian Coast - López Montañez, Ruth; Calero Rios, Emilee Nahomi; Quispe Matos , Kenyi Rolando; Huasasquiche Sarmiento, Lucero; Lastra Paucar, Sphyros Roomel; La Torre , Braulio; Solórzano Acosta, Richard Andi (MDPI, 2025)
Disclaimer/Publisher’s Note: The statements, opinions and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s). MDPI and/or the editor(s) disclaim responsibility for any injury to people or property resulting from any ideas, methods, instructions or products referred to in the content.